Exchange interactions of in the ab plane for An EPR linewidth study - V. Likodimos; Guskos, N.; Garmari-Seale, H. (Physical Review B - Condensed Matter and Materials Physics, 1998)
The electron paramagnetic resonance (EPR) linewidth of (Formula presented) in (Formula presented) is studied as a function of Er concentration. The EPR spectrum complies with the crystal-field ground doublet, while linewidth analysis shows the presence of exchange narrowing. Comparison of the theoretical EPR linewidth with the experimental data provide evidence for the presence of nearest-neighbor exchange interactions of the order of 1 K, most probably anisotropic along the a and b crystallographic axes. © 1998 The American Physical Society.
cited By 8